The effect of detraining and reduced training on the physiological adaptations to aerobic exercise training - Neufer, P. D. (Sports Medicine, 1989)
Even if an individual has a good history of prolonged aerobic training, performance decreases at both the submaximal and maximal levels within weeks of training cessation. Losses coincide with declines in cardiovascular function and metabolic potential. The initial rapid decline in VO2max is related to a decline in maximum cardiac output, which appears to be a functional decline in stroke volume with little or no change in heart rate.